The Role of Motivation in Mediating the Influence of Principal Leadership, Work Environment, and Teacher Competence on the Performance of Elementary School Teachersin Sirampog District - Cakhyadi; Oktarina, Nina (Educational Management, 2025)
This study aims to examine the role of motivation in mediating the influence of principal leadership, work environment, and teacher competence on the performance of elementary school teachers in Sirampog District. By using quantitative research method based on survey approach, data were collected through valid and reliable questionnaires from 207 elementary school teachers in the region. Data were analyzed using multiple regression, Sobel mediation test, and path analysis. The results showed that principal leadership, work environment, and teacher competence have a positive and significant effect on teacher performance. In addition, motivation acts as a mediator that strengthens the influence of these variables on teacher performance. The findings indicate that increasing motivation as well as inspiring and supportive leadership is essential to improve teacher performance in the elementary school environment. The practical implications of this study suggest that principals, school managers and local governments should pay attention to motivational factors and teacher competency development as an effort to improve the quality of primary education.